2020
DOI: 10.1186/s40942-020-00258-5
|View full text |Cite
|
Sign up to set email alerts
|

Use of an ultra-clean air flow for surgical field asepsis when performing intravitreous injections in an ambulatory surgical environment

Abstract: Background Intravitreal injection of medications is one of the most common procedures performed in ophthalmology. Intravitreal anti-VEGF agents are currently the chosen treatment for ocular fundus diseases, including age-related macular degeneration and diabetic retinopathy. As an invasive procedure it involves risks. The most serious complication from intravitreal injection of anti-VEGF agents is endophthalmitis (EO). Although rare, EO can result in devastating loss of vision. This article evaluates whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Previous studies have demonstrated that the use of ultraclean air flow close to the operating table prevented the growth of pathogenic bacteria and should be considered as an alternative to ORs to avoid contamination of materials and drugs. 14 Our results show different advantages from using the laminar flow, primarily, a reduction in the waiting time needed to perform the IVI. Although the IVI is a procedure already performed in the office in several countries, 1,[13][14][15] in Italy and Southern Europe IVIs are still preferably performed in the OR.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Previous studies have demonstrated that the use of ultraclean air flow close to the operating table prevented the growth of pathogenic bacteria and should be considered as an alternative to ORs to avoid contamination of materials and drugs. 14 Our results show different advantages from using the laminar flow, primarily, a reduction in the waiting time needed to perform the IVI. Although the IVI is a procedure already performed in the office in several countries, 1,[13][14][15] in Italy and Southern Europe IVIs are still preferably performed in the OR.…”
Section: Discussionmentioning
confidence: 66%
“…14 Our results show different advantages from using the laminar flow, primarily, a reduction in the waiting time needed to perform the IVI. Although the IVI is a procedure already performed in the office in several countries, 1,[13][14][15] in Italy and Southern Europe IVIs are still preferably performed in the OR. 50 Notably, IVIs performed outside the OR did not increase the percentage of infections.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation